A Brief Account of Animism in Biblical Studies. (26th June 2020) - Joerstad, Mari
Abstract : The study of animism influenced early to mid-twentieth-century biblical scholars, especially on the topic of how ancient Israelites related to nature. Since then, biblical studies have paid less attention to animism, though assumptions about what animism is and how it relates to monotheism continue to shape discussions about nature in the Hebrew Bible. However, since attention to animism has been scant in recent biblical scholarship, these assumptions reflect descriptions of animism put forward by scholars like Edward Burnett Tylor and James George Frazer, which speak of animism as an early and primitive form of religion, inferior to European religions. Biblical scholars doing work in the field of Bible and ecology should instead look to 'new animism'. Attention to 'new animism' can contribute to interpretations of otherwise difficult biblical texts, provide tools of environmental ethics, and perhaps improve dialogues with indigenous communities.